2022
DOI: 10.1136/bmjopen-2021-053964
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence and exacerbations in patients with asthma initiating treatment with inhaled corticosteroids and beta-adrenergic agonists: retrospective cohort study

Abstract: ObjectiveTo determine treatment persistence and exacerbations in patients initiating inhaler treatment with fixed-dose combinations of inhaled corticosteroids/long-acting beta-2-adrenergic agonists (ICS/LABA) for the treatment of asthma.DesignRetrospective observational study conducted by review of electronic medical records (database: Fundación RediSS).SettingRetrospective cohort study. The follow-up period was 1 year.ParticipantsThe study included patients aged ≥18 years who started treatment with ICS/LABA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Primary variable, PDC Patients receiving FF/VI OD demonstrated higher PDC and probability of achieving a clinically significant level of adherence, as well as lower risk of discontinuation compared with those receiving BUD/FOR BID Parimi et al, 2020 [ 28 ] Retrospective new-user, active comparator database FF/VI 100/25 µg OD FF/VI 200/25 µg OD BUD/FOR 100/6 µg (MART/BID) a BUD/FOR 200/6 µg (MART/BID) a BUD/FOR 400/12 µg (MART/BID) Comparison of treatment persistence. Primary variable, time to discontinuation Patients who initiated FF/VI OD were less likely to discontinue treatment and showed greater treatment adherence (higher mean PDC) than patients who initiated BUD/FOR BID Sicras-Mainar et al, 2022 [ 29 ] Observational, retrospective FF/VI 100/25 µg OD FF/VI 200/25 µg OD BUD/FOR 200/6 µg BID BUD/FOR 200/6 µg BID × 2 BUD/FOR 400/12 μg BID × 2 Main endpoints (not stated as primary): comparison of treatment persistence (6- and 12-month rate), % MPR (number of days of medication dispensed by number of days on treatment), and exacerbations (mean no., no. per year, % patients with event) Compared with BUD/FOR BID, FF/VI OD was associated with significantly increased treatment persistence and MPR, resulting in a lower percentage of patients reporting exacerbations (mean number of exacerbations was similar between groups) Stanford et al, 2019 [ 31 ] Retrospective cohort FF/VI 100/25 μg OD BUD/FOR 160/4.5 µg BID Adherence, measured by PDC; persistence, measured by time to index treatment discontinuation; and AMR Patients initiating once-daily FF/VI were more likely to be adherent and have an AMR ≥ 0.5, and were less likely to discontinue therapy compared with patients initiating twice-daily BUD/FOR Dal Negro et al, 2018 [ 27 ] Observational, retrospective FF/VI 100/25 μg OD b Efficacy of FF/VI OD over 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary variable, PDC Patients receiving FF/VI OD demonstrated higher PDC and probability of achieving a clinically significant level of adherence, as well as lower risk of discontinuation compared with those receiving BUD/FOR BID Parimi et al, 2020 [ 28 ] Retrospective new-user, active comparator database FF/VI 100/25 µg OD FF/VI 200/25 µg OD BUD/FOR 100/6 µg (MART/BID) a BUD/FOR 200/6 µg (MART/BID) a BUD/FOR 400/12 µg (MART/BID) Comparison of treatment persistence. Primary variable, time to discontinuation Patients who initiated FF/VI OD were less likely to discontinue treatment and showed greater treatment adherence (higher mean PDC) than patients who initiated BUD/FOR BID Sicras-Mainar et al, 2022 [ 29 ] Observational, retrospective FF/VI 100/25 µg OD FF/VI 200/25 µg OD BUD/FOR 200/6 µg BID BUD/FOR 200/6 µg BID × 2 BUD/FOR 400/12 μg BID × 2 Main endpoints (not stated as primary): comparison of treatment persistence (6- and 12-month rate), % MPR (number of days of medication dispensed by number of days on treatment), and exacerbations (mean no., no. per year, % patients with event) Compared with BUD/FOR BID, FF/VI OD was associated with significantly increased treatment persistence and MPR, resulting in a lower percentage of patients reporting exacerbations (mean number of exacerbations was similar between groups) Stanford et al, 2019 [ 31 ] Retrospective cohort FF/VI 100/25 μg OD BUD/FOR 160/4.5 µg BID Adherence, measured by PDC; persistence, measured by time to index treatment discontinuation; and AMR Patients initiating once-daily FF/VI were more likely to be adherent and have an AMR ≥ 0.5, and were less likely to discontinue therapy compared with patients initiating twice-daily BUD/FOR Dal Negro et al, 2018 [ 27 ] Observational, retrospective FF/VI 100/25 μg OD b Efficacy of FF/VI OD over 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are supported by an analysis of data from phase 2/3 trials of FF in asthma, which demonstrated significant increases in FEV 1 compared with placebo, without any evidence of cortisol suppression at 100 µg and 200 µg OD [ 57 ]. Four RWD studies demonstrated that the initiation of regular FF/VI OD dosing led to generally better treatment persistence or adherence than regular ICS/FOR dosing [ 26 , 28 , 29 , 31 ]. Consequently, real-world evidence to date has shown that FF/VI provided benefits for lung function, asthma control, and reduced reliever use and risk of exacerbations compared with regular ICS/FOR [ 27 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations